2023
DOI: 10.1007/s00018-023-04907-4
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis and EMT: key targets for combating cancer progression and therapy resistance

Yuqing Ren,
Xiangrong Mao,
Hui Xu
et al.

Abstract: Iron-dependent lipid peroxidation causes ferroptosis, a form of regulated cell death. Crucial steps in the formation of ferroptosis include the accumulation of ferrous ions (Fe2+) and lipid peroxidation, of which are controlled by glutathione peroxidase 4 (GPX4). Its crucial role in stopping the spread of cancer has been shown by numerous studies undertaken in the last ten years. Epithelial–mesenchymal transition (EMT) is the process by which epithelial cells acquire mesenchymal characteristics. EMT is connect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 169 publications
0
6
0
Order By: Relevance
“…Research also indicates that ferroptosis can directly increase the expression of COX2 and enhance the secretion of inflammatory signals. Inflammatory compounds stimulate late-stage transcription factors such as Smads, NF-κB, STAT3, Snail, Twist, and ZEB promoting EMT [ 38 ]. Studies has shown that TGF-β promotes the expression of NOX4 in rat LECs and inhibition of NOX4 can block the EMT process [ 39 , 40 ], also DAS et al [ 41 ] proposed that the deletion of NOX4 is in both in vitro and in vivo only a partial repeal of the EMT response, which it was clear that other sources of reactive oxygen species (ROS) have an impact in the EMT process of LECs.…”
Section: Discussionmentioning
confidence: 99%
“…Research also indicates that ferroptosis can directly increase the expression of COX2 and enhance the secretion of inflammatory signals. Inflammatory compounds stimulate late-stage transcription factors such as Smads, NF-κB, STAT3, Snail, Twist, and ZEB promoting EMT [ 38 ]. Studies has shown that TGF-β promotes the expression of NOX4 in rat LECs and inhibition of NOX4 can block the EMT process [ 39 , 40 ], also DAS et al [ 41 ] proposed that the deletion of NOX4 is in both in vitro and in vivo only a partial repeal of the EMT response, which it was clear that other sources of reactive oxygen species (ROS) have an impact in the EMT process of LECs.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the inclusion of HIF while inhibiting GPX4 mitigates GPX4-mediated ferroptosis. HIF-1α and HIF-2α have been identified as regulators of ferroptosis in renal clear cell carcinoma cells [ 107 ]. Inducing the expression of HIF-1α through increasing the expression of fatty acid-binding proteins 3 and 7 under hypoxic conditions inhibits ferroptosis [ 108 ].…”
Section: Ferroptosis and Cancermentioning
confidence: 99%
“…Highly mesenchymal stem cells confer drug-resistant properties to different cancer types. A growing body of clinical evidence suggests that targeting ferroptosis holds promise as a potential strategy to overcome drug resistance and augment the therapeutic effectiveness of anticancer treatments ( 12 ). Ferroptosis inducers demonstrate the ability to reverse acquired resistance in cancer cells to various anticancer agents such as lapatinib, cisplatin, docetaxel, sorafenib, among others.…”
Section: Introductionmentioning
confidence: 99%